**Q.)Let g(x) be a function such that g(x+1)+g(x-1)=g(x) for every real x. Then for what value of p is the relation g(x + p)=g(x) necessarily true for every real x?
**(a)5 (b)3 (c)2 (d)6

Answer:

g(x+1) + g(x-1) =g(x)

g(x+2) + g(x) =g(x+1)

Adding the above two, we get

g(x+2) + g(x-1) =0 ——(i)

g(x+3) + g(x)=0

g(x+4) + g(x+1)=0

g(x+5) + g(x+2)=0 ——(ii)

From equation (i) and (ii), we get

g(x+5)= g(x-1)

Putting x+1 in place of x, we get

=>g(x+6) = g(x)

Hence, the required value of p=6

Fenster[…]here are some links to internet sites that we link to mainly because we think they are worth visiting[…]